Proteção constitucional do trabalhador portador de incapacidade laboral - Morais, Lindocastro Nogueira de (2013)
Social security has constitutional protection and encompasses health policies, social security and welfare, which are explicitly recognized as a fundamental social right. When workers suffering from work disability are unable to earn income with your work force to support themselves and their families. The State, through the public welfare, contributory and compulsory, has a duty to protect workers in times of misfortune, replacing these income through the provision of social security benefits. Disability the employee has a higher degree of vulnerability, and the granting of disability claims a right sensitive, which can‟t suffer postponements, lest cause legal uncertainty and violating the dignity of the human person. There isn‟t legal definition of disability. The main purpose of the study is the constitutional protection of the worker carrying work disability, seeking to highlight the factors affecting work disability and proposing the use of objective criteria for the grant of social security benefits, because the criteria used are purely medical, based the subjectivity and agency of medical assessor, which hinders the judicial and administrative control of the State. At the time of preparing the expert report, the expert should not consider only tangible aspects, but also social and environmental issues, which contribute to the inability to work and therefore should be considered in granting social security benefits. The granting of social security benefits for incapacity for work is intended to prevent or lessen the impact of individual and social risks in relation to the worker incapacitated, ensuring that the constitutional protection to be effective. The presumed inability, the institute reversing the burden of proof and free conviction motivated are important tools for resolving conflicts between the insured and welfare, finding basis in the insured`s vulnerability, sensitivity and little reliance right at issue in relation to the employee social pension